Daily differential expression of melatonin‐related genes and clock genes in rat cumulus–oocyte complex: changes after pinealectomy. Issue 4 (4th April 2015) - Coelho, L. A.; Peres, R.; Amaral, F. G.; Reiter, R. J.; Cipolla‐Neto, J.
Abstract This study investigated the maturational stage (immature and mature ovaries) differences of mRNA expression of melatonin‐forming enzymes (Aanat and Asmt), melatonin membrane receptors (Mt1 and Mt2) and putative nuclear (Rorα) receptors, and clock genes (Clock, Bmal1, Per1, Per2, Cry1, Cry2) in cumulus–oocyte complexes (COC) from weaning Wistar rats. We also examined the effects of pinealectomy and of melatonin pharmacological replacement on the daily expression of these genes in COC. qRT‐PCR analysis revealed that in oocytes, the mRNA expression of Asmt, Mt2, Clock, Bmal1, Per2, and Cry1 were higher (P < 0.05) in immature ovaries than in the mature ones. In cumulus cells, the same pattern of mRNA expression for Asmt, Aanat, Rorα, Clock, Per1, Cry1, and Cry2 genes was observed. In oocytes, pinealectomy altered the daily mRNA expression profiles of Asmt, Mt1, Mt2, Clock, Per1, Cry1, and Cry2 genes. In cumulus cells, removal of the pineal altered the mRNA expression profiles of Mt1, Mt2, Rorα, Aanat, Asmt, Clock, Bmal1, Per2, Cry1, and Cry2 genes. Melatonin treatment partially or completely re‐established the daily mRNA expression profiles of most genes studied. The mRNA expression of melatonin‐related genes and clock genes in rat COC varies with the maturational stage of the meiotic cellular cycle in addition to the hour of the day. This suggests that melatonin might act differentially in accordance with the maturational stage of cumulus/oocyte complex. In addition, it seems that circulating pineal melatonin is very important in the design of the daily profile of mRNA expression of COC clock genes and genes related to melatonin synthesis and action.